Returning to the Conversation: Meta- or Inter-? - Sverdiolas, Arūnas (Problemos, 2016)
The paper examines some fundamental notions recurrent throughout Algis Mickūnas’s works and related to the issue of the possibility of a metacultural and metacivilizational thought. The originality of Mickūnas’s approach to intercultural studies lies in his reformulation of its problematics in the conceptual framework of transcendental phenomenology. He regards cultures, traditions, and civilizations as coded or symbolic expressions of consciousness, and holds that other civilizations may be accessed by way of the phenomenological eidetic analysis of the essentially polycentric consciousness. The fundamental plane of such consciousness is defined by relationships between permanence and flux, found operative in a wide range of forms, of which Mickūnas draws a full paradigm. The paper considers whether these structures of consciousness and their relations are the only possibility, and what precisely grounds the hierarchies of the eidetics in place.
Keywords: permanence; flux; civilisation studies; Mickūnas; Kavolis